A new approach to estimating household night consumption at DMA level - Loureiro, D. (2012)
The most widely used method for assessing real water losses in a district metering area (DMA) involves measuring minimum night flow and estimating what fraction of it is not ascribed to real losses. It may be further broken down into authorized household consumption, authorized non-household consumption and non-authorised uses. Household consumption is in general the most relevant and harder to estimate component. It is very much context-dependent and very few studies are published outside of the UK. This paper summarises the results achieved in a recent study carried out in two Portuguese municipalities, and describes a set of simplified rules developed to predict DMA night household consumption. These rules depend on the number of households and on their social-demographic and billing features. Once household night consumption is estimated, it can then be deducted from to minimum nigh flow monitored in a DMA or part of a DMA, contributing to a more accurate estimate of real water losses. The results obtained show significant differences from case to case, but in most cases lower values than the published UK references. This is believed to show that residential night consumption is rather context-dependent and that real losses may in fact be higher than estimated so far in this region.